Flag brands as factor and results of a country identity and image: Polish experiences - Nikodemska-Wolowik, Anna Maria (Pecvnia : Revista de la Facultad de Ciencias Económicas y Empresariales, Universidad de León, 2006)
This article discusses the issue of creating regional and country brands by enterprises and of establishing a national brand. The three mentioned flag brand categories have been described in detail and the relations between them have been indicated. The article also makes an attempt at analyzing the factors that form part of the brand identity focusing primarily on the consumer product brands. The identity and image concepts are presented also in a broader perspective as certain attributes that characterize the enterprise itself. The presented considerations refer mainly to Polish companies, but some examples of enterprises from highly developed countries, especially from the European Union, have also been added in order to provide this paper with more practical dimensions. Specific brands offered by national enterprises that may be called country and regional brands have been proposed. Some transformations of the market environment which imply branding activities of the companies have been identified, especially the antiglobalist movement which becomes more and more powerful and its activities directed against big concerns and omnipresent mass brands. Moreover, the consumer ethnocentrism and regional trends opposed to the globalization have been emphasized. Also the important rote of family businesses in developing flag brands has been made evident. The family companies may contribute to maintaining and reinforcing the Polish identity. El presente trabajo se ocupa de los aspectos referentes a la creación de marcas regionales y locales así como del establecimiento de una marca nacional. Las tres categorías de marcas de bandera se han caracterizado detalladamente y se indican las relaciones que existen entre ellas. También se intenta analizar los factores que forman parte de la identidad de marca, con especial atención a las marcas de productos de consumo. Se presentan los conceptos de identidad e imagen desde una perspectiva más amplia como atributos que caracterizan a la empresa. Las reflexiones presentadas se refieren, sobre todo, a las empresas polacas, pero también se citan algunos ejemplos de actividades de compañías localizadas en países altamente desarrollados, en concreto en la Unidad Europea, con el fin de otorgar al artículo una dimensión práctica. Se proponen marcas concretas que ofrecen empresas locales y que pueden denominarse como marcas nacionales o regionales. Se indican los cambios en el entorno del mercado que implican actividades de las empresas en el área de branding, y de modo especial se toma en consideración el cada vez más fuerte movimiento antiglobalizante y sus actividades dirigidas contra grandes consorcios y las omnipresentes marcas de masas. Además se pone de relieve el significado de etnocentrismo de tos consumidores y de las tendencias regionalistas opuestas a la globalización. Del mismo modo, se destaca el importante papel de las empresas familiares en el establecimiento de marcas de bandera. Las empresas familiares podrán contribuir a conservar y reforzar la identidad polaca